CHANGES IN ORAL MICROBIOME DURING NON-SURGICAL THERAPY OF PATIENTS WITH SEVERE PERIODONTITIS - J Myšák; Š Podzimek; T Janatová; J Dušková; J Janata; L Najmanová (Czech Dental Chamber, 2021)
Introduction, aim: Periodontitis, which is one of the most common diseases in the adult population, is almost as common cause of tooth loss in people over the age of 35 as it is due to tooth decay. The aim of this study was to evaluate the utility of new-generation sequencing methods as a tool for complex characterization of subgingival bacterial biofilm in patients with advanced periodontitis and for monitoring the dynamics of changes in the composition of subgingival bacterial biofilm during therapy. We assume that next-generation sequencing methods will provide a new quality of monitoring the course of treatment and offer periodontologists a tool for objective evaluation of the effectiveness of the chosen therapeutic procedure and choice of further treatment. Methods: The study included 43 patients with a diagnosis of advanced periodontitis. Patients were divided into two subgroups and treated with one of two standard approved methods - deep scaling and root planing only (subgroup A - 20 patients) and deep scaling and root planing supplemented with antibiotic therapy (subgroup B - 23 patients) - and their periodontal status was assessed by periodontal indices BOP (bleeding on probing), CAL (clinical attachment loss) a PPD (periodontal pocket depth) before treatment and two weeks, three months and 18 months after therapy. A set of four samples was taken from each deepest periodontal pocket at equal time intervals to determine the microbiome composition. Results: During treatment, there was a significant decrease in the periodontal indices PPD, BOP and CAL in both subgroups of patients. There was also a significant decrease in the periodontal risk index R/G during treatment. In addition, the subgroup of patients treated with deep scaling and root planing with antibiotics (subgroup B) had a significantly higher decrease in R/G index 14 days after treatment compared to subgroup A treated with deep scaling and root planing alone. Three months and 18 months after treatment, the periodontal risk index R/G values were similar in both subgroups of patients. Conclusion: Taxonomic characterization of the microbiome expressed in the form of R/G index allows to monitor dynamic changes during treatment, in contrast to mere monitoring of clinical parameters shows clear differences between groups with and without antibiotics at 14 days after deep scaling and root planing therapy. However, given the clinical parameters of the two groups, which do not differ significantly after three or 18 months, it is appropriate to carefully consider whether antibiotic support for deep scaling and root planing is beneficial, as there is a significant risk of developing and spreading resistance. The use of antibiotics in periodontology should be based on detailed clinical, microbiological and general medical examination.